Code-Switching And Code-Mixing In English Language Teaching And Learning At SMA Negeri 2 Kendari - Arlan, Arlan; Sailan, Zalili; Lio, Asrun (Halu Oleo University, 2019)
Many people speak and switch or mix their general use of language with their mother tongues, especially in communicating with people. This study is aimed to describe the types of code-switching and code-mixing; why do teachers mix code and switch code; and reasons and impact on students of code-switching and code-mixing by teachers and students in the English as second language (ESL), SMA Negeri 2 Kendari. Accordingly, 65 students at the high school level and three of their instructors in EFL classrooms took part in the study. Data were collected through observations, questionnaires to teachers, and interviews with selected sample students. The result of qualitative and quantitative design analysis showed that code-mixing and code-switching types dominantly used by teachers were intrasentential switching and allowed intersentential switching. And teachers used more dominant of intrasentential mixing types. The reasonâ€™s teachers to Â switching and mixing implementation were directing or conveying some explanations effectively, it is used cause forget some terms so as achieving a good learning process, to explain or give an understanding to students if they feel have not understood the lessons given so switching to Indonesian is an important communication strategy, more effective and expected to get a better relationship between them. Finally, the results of reason and impact on students by Â descriptive questionnaire analysis showed that the students that lack ability in the target language, it's difficult to get the equivalent of the words on target language or find new words or terms in the context, and they did it unconsciously from English utterance to Indonesian and make students more understand when doing of switch code and mix code in English learning process.